Recent Advances in Host-Directed Therapies for Tuberculosis and Malaria - Matteucci, Kely C.; Correa, André A. S.; Costa, Diego L. (Frontiers in cellular and infection microbiology, 2022)
Tuberculosis (TB), caused by the bacterium Mycobacterium tuberculosis , and malaria, caused by parasites from the Plasmodium genus, are two of the major causes of death due to infectious diseases in the world. Both diseases are treatable with drugs that have microbicidal properties against each of the etiologic agents. However, problems related to treatment compliance by patients and emergence of drug resistant microorganisms have been a major problem for combating TB and malaria. This factor is further complicated by the absence of highly effective vaccines that can prevent the infection with either M. tuberculosis or Plasmodium . However, certain host biological processes have been found to play a role in the promotion of infection or in the pathogenesis of each disease. These processes can be targeted by host-directed therapies (HDTs), which can be administered in conjunction with the standard drug treatments for each pathogen, aiming to accelerate their elimination or to minimize detrimental side effects resulting from exacerbated inflammation. In this review we discuss potential new targets for the development of HDTs revealed by recent advances in the knowledge of host-pathogen interaction biology, and present an overview of strategies that have been tested in vivo , either in experimental models or in patients.